Human Resource Development of Bandung MSMEs with Entrepreneurial Leadership Characteristic through Quality Leadership in Global Market Era - Nina Nurani; Uce Karna Suganda; Nurul Hermina; Deden Sutisna (PT Mattawang Mediatama Solution, 2023)
MSMEs in Bandung has contributes significantly to the economic growth of the city. However, the number of exports is still low. The problems are minimal human resource performance, limited products, less innovative and less than optimal technological capabilities, thus it is necessary to develop entrepreneurial leadership characters in the global market as a strategy for competitiveness and implementing a learning culture. The aim of this study is to find out how the development of human resources in MSMEs in Bandung has entrepreneurial leadership characteristics in entering the global market. This study is carried out using cross sectional method. The specification of this study is descriptive quantitative analysis, using purposive sampling technique to produce a total of 85 respondents. Data collection techniques is using literature studies, questionnaires, interviews, and observations. The results showed that the development of MSME human resources in Bandung with entrepreneurial leadership characteristics with the Cognitive Ambidexterity approach, SEER (Social, Environmental, and Economic Responsibility and Sustainability), SSA (Self and Social Awareness), entrepreneurial leadership and the quality of